1985
DOI: 10.1104/pp.77.2.329
|View full text |Cite
|
Sign up to set email alerts
|

Electrogenic Proton Translocation by the ATPase of Sugarcane Vacuoles

Abstract: Existence of a proton-translocating ATPase on the tonoplast of higher plants has been further confirmed by use of two experimental systems: (a) intact isolated vacuoles from sugarcane cells and (b) vesicles prepared from the same source. Addition of MgATP to vacuoles polarized the tonoplast by 40 millivolts to a value of +20 millivolts, but a large preexisting pH gradient across the membrane restricted the pH change to 0.2 unit. In vesicle preparations, the tonoplast was polarized to +66 millivolts by the addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

1987
1987
2017
2017

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…However, the vacuole preparations were apparently defective; sucrose was taken up by the isolated vacuoles at a rate 10 times less than the in situ uptake rate and 100 times less than that of 3-OMG (Thom et al 1982b). Nevertheless, tonoplast vesicles isolated from the vacuoles confirmed the functioning of a H+-pumping ATPase capable of maintaining a protonmotive potential difference of 125 mV (Thom and Komor 1985). This is comparable with the protonmotive values for other plants (see review by Bush 1993).…”
Section: Membrane Transportsupporting
confidence: 77%
See 1 more Smart Citation
“…However, the vacuole preparations were apparently defective; sucrose was taken up by the isolated vacuoles at a rate 10 times less than the in situ uptake rate and 100 times less than that of 3-OMG (Thom et al 1982b). Nevertheless, tonoplast vesicles isolated from the vacuoles confirmed the functioning of a H+-pumping ATPase capable of maintaining a protonmotive potential difference of 125 mV (Thom and Komor 1985). This is comparable with the protonmotive values for other plants (see review by Bush 1993).…”
Section: Membrane Transportsupporting
confidence: 77%
“…These results indicated that sugarcane has a tonoplast-bound ATPase that translocates protons into the vacuole thereby generating the ;+ H+ H+ proton gradient (Thom and Komor 1985) needed for operating a hexose H+-antiport system ([3] of Fig. 4) (Thom and Komor 198417).…”
Section: Membrane Transportmentioning
confidence: 99%
“…On one side, addition of sucrose in presence of MgATP to vacuoles from sugarcane stalk gave barely perceptible uptake of sucrose (14), while on the other hand MgATP even inhibited the UDP-glucose group translocator (26). The delicate coexistence of tonoplast energization by the ATPase (22) and sucrose storage by the UDP-glucose group translocator was puzzling, especially in the case of sugar beet vacuoles, where the coexistence of the proton-driven sucrose-proton antiport system and the UDP-glucose group translocator was visualized (23). Therefore, as a first step to obtain ideas about the mutual interaction of energization and sucrose storage, a careful analysis of the reaction products, which are produced by incubation of sugarcane vacuoles with UDP-glucose, was performed.…”
mentioning
confidence: 99%
“…Thus, measurements were performed on cell types amenable to microelectrodes, like root cells, mesophyll cells, or unicellular green algae, and using fluorescent dyes on isolated vacuoles. The reported transtonoplast potential values varied between 0 and 266 mV (Thom and Komor, 1985;Bethmann et al, 1995;Walker et al, 1996;Miller et al, 2001;Wang et al, 2015). In Arabidopsis, measurements of tonoplast potentials in mesophyll and root hair cells yielded a value of about 230 mV (Miller et al, 2001;Wang et al, 2015).…”
Section: The Vacuolar Membrane Potential During Stomatal Movementmentioning
confidence: 99%